Development of smash accuracy instruments in table tennis - Suhermon, Suhermon; Arisman, Arisman; Tofikin, Tofikin; Siska, Siska; Hendryanto, Ferri; Indah, Debby; Haryanto, Jeki (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problem: The problem in this study is that there is no new smash instrument in table tennis. Purpose: The purpose of this research is to develop smash instrument in table tennis. Methods: This research method is Research and Development (R&D). The population and sample in this study were 20 PTM Pasir Pengaraian table tennis athletes. The data collection methods in this study included questionnaires and measurement tests. Questionnaires were distributed to material and media experts to assess the feasibility of the table tennis smash test instrument. The tests were conducted to determine the validity and reliability of the smash test instrument. Reliability was assessed by correlating the results of the first smash test with those of the second, while validity was established by correlating the results of the first smash test with the criterion test. The criterion test involved field judges' evaluations using a smash assessment matrix. Data analysis was performed using the product-moment correlation formula. Results: The results of the study were obtained from material experts 82% and 85% (appropriate), media experts 88% and 86% (decent). Validity 0.89 and reliability 0.84, indicating valid and reliable based on the Kirkendall category. Conclusion: This study successfully developed a new smash test instrument for table tennis, which was deemed appropriate and feasible by experts. The instrument demonstrated high validity (0.89) and reliability (0.84), making it suitable for assessing smash performance.